2012
DOI: 10.1021/bc200672s
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Fluorescent Labeling and Oriented Immobilization of a Triple Mutant of CYP3A4 via C64

Abstract: The generation of site-specific bioconjugates of proteins is highly desired for a number of biophysical and nanotechnological applications. To this end, many strategies have been developed that allow the specific modification of certain canonical amino acids and, more recently, noncanonical functional groups. P450 enzymes are heme-dependent monooxygenases involved in xenobiotic metabolism and in the biosynthesis of a variety of secondary metabolites. We became interested in the site-specific modification of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…This approach has been used by Ménard et al . for the oriented immobilization of a human cytochrome P450 enzyme (CYP3 A4) to commercial resin or silica microspheres . The reaction between the thiol and maleimide occurs spontaneously, without the need for added reagents, and with high specificity to give a stable linkage at pH 6.5 to 7.5 making this a very efficient way to immobilize the enzyme variants.…”
Section: Resultsmentioning
confidence: 99%
“…This approach has been used by Ménard et al . for the oriented immobilization of a human cytochrome P450 enzyme (CYP3 A4) to commercial resin or silica microspheres . The reaction between the thiol and maleimide occurs spontaneously, without the need for added reagents, and with high specificity to give a stable linkage at pH 6.5 to 7.5 making this a very efficient way to immobilize the enzyme variants.…”
Section: Resultsmentioning
confidence: 99%
“…A similar trend was observed for the C98S/C239S/C468G mutant of Δ3–12 CYP3A4, reported to possess a 1.5-fold higher activity than WT. 17 …”
Section: Resultsmentioning
confidence: 99%
“…9 Menard and co-workers reported that the C98S/C239S/C468G mutant is 1.5-fold more active than the WT and undergoes maleimide modification primarily at the Cys64 site without a significant loss of the enzymatic activity. 17 Based on the latter mutant, a poorly expressed C58T/C64A/C98S/C239S/C468G variant was built for mechanistic studies of the allostery and binding cooperativity in CYP3A4. 18 Another group investigated C64S/C98S, C98S/C377S/C468G, C98S/C239S/C468G, C98S/C239S/C377S/C468A, and C58T/C64A/C98S/C239S/C377S/C468A variants 6,7,9,10,12 and noticed that elimination of more than four native cysteines markedly lowers the level of CYP3A4 expression.…”
mentioning
confidence: 99%
“…Wild type CYP3A4 and the C215 mutant were expressed and purified as previously described, with minor modifications [34,36]. Wild type refers to the N-terminus-truncated Δ2–12 CYP3A4, which was used as a template for preparation of the C215 mutant containing the following mutations: C58T/C64A/C98S/F215C/C239S/C468G.…”
Section: Methodsmentioning
confidence: 99%